Search for steady point-like sources in the astrophysical muon neutrino flux with 8 years of IceCube data - IceCube Collaboration; Aartsen, MG; Ackermann, M; Adams, J; Aguilar, JA; Ahlers, M; Ahrens, M; Altmann, D; Andeen, K; Anderson, T; Ansseau, I; Anton, G; et al. (Springer Berlin Heidelberg, 2019)
The IceCube Collaboration has observed a highenergy astrophysical neutrino flux and recently found evidence for neutrino emission from the blazar TXS 0506+056. These results open a new window into the high-energy universe. However, the source or sources of most of the observed flux of astrophysical neutrinos remains uncertain. Here, a search for steady point-like neutrino sources is performed using an unbinned likelihood analysis. The method searches for a spatial accumulation of muon-neutrino events using the very high-statistics sample of about 497,000 neutrinos recorded by IceCube between 2009 and 2017. The median angular resolution is ∼ 1◦ at 1 TeV and improves to ∼ 0.3◦ for neutrinos with an energy of 1 PeV. Compared to previous analyses, this search is optimized for point-like neutrino emission with the same flux-characteristics as the observed astrophysical muon-neutrino flux and introduces an improved event-reconstruction and parametrization of the background. The result is an improvement in sensitivity to the muon-neutrino flux compared to the previous analysis of ∼ 35% assuming an E−2 spectrum. The sensitivity on the muon-neutrino flux is at a level of E2dN/dE = 3 · 10−13 TeV cm−2 s−1. No new evidence for neutrino sources is found in a full sky scan and in an a priori candidate source list that is motivated by gamma-ray observations. Furthermore, no significant excesses above background are found from populations of sub-threshold sources. The implications of the non-observation for potential source classes are discussed.